Effectiveness of PBL Model Based on Local Wisdom on Children's Scientific Thinking Skills - Risnawati, Risnawati; Purwaningsih, Diah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of the problem-based learning model based on local wisdom on scientific thinking skills in children. This research is a type of quantitative research with a meta-analysis approach. This meta-analysis analyzed 23 effect sizes obtained through Google Scholar; Mendeley; ERIC issued in 2022-2025 with 1054 children. Data analysis with the help of the JASP application. Effect size is calculated with a 95% confidence level. The results of the data analysis concluded that the summary effect size value obtained through the random effect model was 1,072 (very high effect size category). These findings show that on average, children who use the problem-based learning model based on local wisdom can improve scientific thinking skills in children compared to conventional learning models.